Exploration, development and exploitation of mining and metallurgical minerals in Peru (LACCEI, 2024)
The purpose of this article was to show the main companies that are currently in the metallurgical mining exploration, development and exploitation stage of Peru. Each stage of these processes was analyzed in detail in the years 2020, 2021 and 2022. The type of research was non-experimental, descriptive, because the data was analyzed and described, evaluating its capital investment at each stage, as a result it was obtained that in 2021, the mining company that made the most investment in exploration was Company de Minas Buenaventura S.A with a total of US$30.8 million, in terms of development and preparation, in 2021 an amount of US$592 million was reported, registering a growth of 52.0% compared to the figure registered in 2020. Lastly, in the month of June 2022, a total of 682 mining companies carries out metallic and non-metallic exploitation works in Peru.